2023
DOI: 10.1155/2023/7082352
|View full text |Cite
|
Sign up to set email alerts
|

A Porcine Epidemic Diarrhea Virus Isolated from a Sow Farm Vaccinated with CV777 Strain in Yinchuan, China: Characterization, Antigenicity, and Pathogenicity

Abstract: Porcine epidemic diarrhea virus (PEDV) is a porcine enteric coronavirus globally, causing serious economic losses to the global pig industry since 2010. Here, a PEDV CH/Yinchuan/2021 strain was isolated in a CV777-vaccinated sow farm which experienced a large-scale PEDV invasion in Yinchuan, China, in 2021. Our results demonstrated that the CH/Yinchuan/2021 isolate could efficiently propagate in Vero cells, and its proliferation ability was weaker than that of CV777 at 10 passages (P10). Phylogenetic analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 50 publications
0
0
0
Order By: Relevance
“…Additionally, another study reported that the non-S-INDEL PEDV HM2017 strain caused clinical symptoms in piglets at 12 hpi, and they all died at 84 hpi [43]. In our lab, the PEDV CH/Yinchuan/2021 strain infected pig populations of all ages and caused 100% mortality in 3-day-old piglets [42]. Moreover, we found that 13-week-old growing pigs infected with PEDV experienced watery diarrhea and vomiting and significantly reduced weight gain despite low mortality (unpublished data).…”
Section: Pedv Pathogenicitymentioning
confidence: 54%
See 4 more Smart Citations
“…Additionally, another study reported that the non-S-INDEL PEDV HM2017 strain caused clinical symptoms in piglets at 12 hpi, and they all died at 84 hpi [43]. In our lab, the PEDV CH/Yinchuan/2021 strain infected pig populations of all ages and caused 100% mortality in 3-day-old piglets [42]. Moreover, we found that 13-week-old growing pigs infected with PEDV experienced watery diarrhea and vomiting and significantly reduced weight gain despite low mortality (unpublished data).…”
Section: Pedv Pathogenicitymentioning
confidence: 54%
“…The emerging non-S-INDEL PEDV strains harbor some novel pathogenic features, such as rapid onset, rapid transmission, rapid death, and high mortality. In our investigation, 3-day-old piglets were infected with the identified novel non-S-INDEL strain PEDV CH/Yinchuan/2021, which caused vomiting and diarrhea at 18 hpi, and all the piglets died at 96 hpi (Table 1) [42]. Additionally, another study reported that the non-S-INDEL PEDV HM2017 strain caused clinical symptoms in piglets at 12 hpi, and they all died at 84 hpi [43].…”
Section: Pedv Pathogenicitymentioning
confidence: 71%
See 3 more Smart Citations